2018
DOI: 10.7475/kjan.2018.30.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sleep Quality of Clinical Nurses Working in a Hospital

Abstract: The purpose of this study was to identify factors affecting sleep quality in nurses working in a tertiary hospital in Korea. Methods: The sample of two hundred and sixty three nurses was drawn from one tertiary care hospital in Korea. Using a descriptive study design, clinical nurses completed the standardized questionnaires, including sleep quality, depressive symptoms, and resilience. Descriptive statistics were computed to describe the sample and study variables. Logistic regression analyses were used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Married nurses were found to have shorter sleep duration and sleep latency compared to single nurses, and high job stress not only hinders their family life, but also causes sleep problems [13][14][15][16], highlighting the fact that married female nurses are more vulnerable to sleep problems than other groups. Diminished sleep quality decreases concentration, induces physical diseases, reduces work performance, and increases the risk of medical malpractice, such as medication error, error in medical-device manipulation, error in judgment of patients' states, and needle injuries, as well as deteriorating the quality of care, such as displaying emotional inattention to patients, all of which have an adverse impact on the recovery of patients who received the care [16][17][18][19][20]. Therefore, nurses' sleep quality is an important factor not only for their and patients' health, but also for preventing medical malpractice.…”
Section: Introductionmentioning
confidence: 99%
“…Married nurses were found to have shorter sleep duration and sleep latency compared to single nurses, and high job stress not only hinders their family life, but also causes sleep problems [13][14][15][16], highlighting the fact that married female nurses are more vulnerable to sleep problems than other groups. Diminished sleep quality decreases concentration, induces physical diseases, reduces work performance, and increases the risk of medical malpractice, such as medication error, error in medical-device manipulation, error in judgment of patients' states, and needle injuries, as well as deteriorating the quality of care, such as displaying emotional inattention to patients, all of which have an adverse impact on the recovery of patients who received the care [16][17][18][19][20]. Therefore, nurses' sleep quality is an important factor not only for their and patients' health, but also for preventing medical malpractice.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience activates the positive internal energy of nurses [ 11 , 14 , 15 ], and it is a major attribute that affects the quality of care and organizational efficiency [ 16 ]. Nurses with higher resilience levels actively utilize internal and external resources to overcome difficulties and minimize the negative effects of stress and to improve sleep quality and well-being, resulting in good performance in nursing work [ 17 , 18 ]. However, when the level of resilience is low in nurses, the ability to manage stress effectively decreases, leading to negative consequences such as burnout and increased turnover intent [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we found that on a relational level, the components of sleep quality negatively correlated with stress management and mood, just as occurred in the results found by Lallukka et al [27] and Sin et al [28], where sleep duration was negatively related to both variables in adults. In addition, poor sleep quality led to a decreased capacity for regulating emotions and acted as a risk factor causing mood disorders and deficient stress management in healthcare personnel [26]. This corroborates the existence of a significant association between emotional intelligence factors and sleep quality components.…”
Section: Discussionmentioning
confidence: 65%
“…People who work on different shifts also suffer from health disorders [23], for example, in eating patterns [24], which in turn are closely related to sleep quality and self-esteem [25]. At present, poor sleep quality among healthcare professionals is not only a risk factor for performing their services, but a critical problem in the healthcare system [26], which can lead to development of mood disorders and deficient stress management. Thus, some studies have found that the duration and quality of sleep and emotion management by healthcare professionals are closely connected [27,28].…”
Section: Introductionmentioning
confidence: 99%